A death to pay for - Nairn, Charlie; Brady, Shelagh ([S.l.] : Ray Fitz Walter [production company] ; Bristol : BBC Education & Training [distributor], 1996)
Documentary about the Australian aborigines. Described social life and customs of Kawelka people that lives in West Australia. Focus on Ongka, Kawelka Big-Man who is a religious leader
Antropologist, Andrew Strathern ; series producer, David Wason ; series editor, Leslie Woodhead
Keywords: Australian aborigines -- Australia -- Ethnic identity; Australian aborigines -- Social life and customs